Sexual reproduction of yellow ecotype of Neurospora intermedia in nature - A Pandit; P S Dubey; S Mall (Fungal Genetics Reports, 2000)
The vegetative stage of yellow ecotype of Neurospora intermedia occurs on various substrates but there has been no evidence of its telomorphic stage in nature. This paper presents evidence for the sexual reproduction of this ecotype in nature on maize cobs.